If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 + -15 = -15 Reorder the terms: 2 + -15 + 6x = -15 Combine like terms: 2 + -15 = -13 -13 + 6x = -15 Solving -13 + 6x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 6x = -15 + 13 Combine like terms: -13 + 13 = 0 0 + 6x = -15 + 13 6x = -15 + 13 Combine like terms: -15 + 13 = -2 6x = -2 Divide each side by '6'. x = -0.3333333333 Simplifying x = -0.3333333333
| .50c+.40=400 | | -3(x+4)+4=7(x+4)+3 | | 5(x-7)+10=3(x-5) | | h(t)=2t-t^2 | | 5sinx+7cosx=8 | | 12x-8=9x-8 | | x-4=-24-9x | | .50c+400=.40 | | (2x-5)=15 | | -3(t-5)+7t=6t-5 | | 2=x/6.4 | | 6-14=6+(-8) | | (a^4+4a+-8)=0 | | 12x^2y+18xy-6x=0 | | f(x)=15x^4-15x^2 | | a^4+4a-8=0 | | 45=7-2b | | 1/4x0.04 | | 12/7=k//8 | | .50c+.40=190 | | -4=6+2x | | 1.7=k/8 | | Log(x)=-8 | | r-9.8=-2.4 | | 4s=s-3 | | 5y+ax=0 | | x/12=2/8 | | -4x+by=6 | | 8-8x-4=-37+3x-14 | | 2.1y+37.8=7.4y+6 | | -7v+1=-5v+1 | | a+5y=0 |